Process and kinetic analysis of osmium prepared by microwave sintering - LIU Wei; LI Shi-lei; ZHOU Fan; YANG Yun-fei; XIE Yuan-feng; XIA Yang; LÜ Hong; ZHANG Chao; ZHANG Xiao-ke; WANG Jin-shu (Fenmo yejin jishu)
Os sintered body was prepared by microwave sintering process. The influences of the green compact pressure and the microwave sintering parameters (heating rate, sintering temperature, and holding time) on the microstructure and relative density of Os sintered bodies were investigated. The densification mechanism of Os microwave sintering was analyzed. The results show that, the average grain size of Os after microwave sintering at 1350 ℃ is about 0.22 μm, which is close to the average particle size of the Os powders. With the increase of the sintering temperature to 1500 ℃, the grain size grows to 0.76 μm. The relative density of the Os sintered body increases rapidly at first and then slowly after prolonging the holding time sintered at 1500 ℃. After microwave sintering at 1500 ℃ for 60 min, the relative density of the Os sintered body is 94.3%, and the average particle size is less than 1 μm. The sintering kinetics analysis shows that the densification process of Os is the result of the combined action of volume diffusion and grain boundary diffusion. With the increase of the sintering temperature, the diffusion mechanism gradually transfers from grain boundary diffusion to volume diffusion.